Ileal FXR-FGF15/19 signaling activation improves skeletal muscle loss in aged mice. (March 2022) - Qiu, Yixuan; Yu, Jiaming; Ji, Xueying; Yu, Huiyuan; Xue, Mengjuan; Zhang, Fan; Li, Yi; Bao, Zhijun
Highlights: FXR-FGF15/19 signaling in ileum is downregulated in human and mice during aging. Ileal FXR-FGF15/19 signaling is related to skeletal muscle mass. Changes in gut microbiota and microbial bile acid metabolism during aging lead to changes in ileal FXR-FGF15/19 signaling. Intestine-specific FXR agonist fexaramine could be a promising strategy to treat sarcopenia. Abstract: Sarcopenia is the age-related decrease in skeletal muscle mass, and current therapies for this disease are ineffective. We previously showed that ileal farnesoid X receptor (FXR)-fibroblast growth factor 15/19 (FGF15/19) signaling acts as a regulator of gut microbiota to mediate host skeletal muscle. However, the therapeutic potential of this pathway for sarcopenia is unknown. This study showed that ileal FXR-FGF15/19 signaling was downregulated in older men and aged male mice due to changes in the gut microbiota and microbial bile acid metabolism during aging. In addition, the intestine-specific FXR agonist fexaramine increased skeletal muscle mass and improve muscle performance in aged mice. Ileal FXR activation increased skeletal muscle protein synthesis in a FGF15/19-dependent way, indicating that ileal FXR-FGF15/19 signaling is a potential therapeutic target for sarcopenia.